Evaluation of Nuphar lutea as bioindicator of metal pollution in freshwater ecosystems. (March 2022) - Polechońska, Ludmiła; Klink, Agnieszka; Golob, Aleksandra; Germ, Mateja
Abstract: Macrophytes have a capacity to absorb elements from the water and sediment and some species can be bioindicators of pollution. The uptake of 12 metals by Nuphar lutea from 56 water bodies was studied to evaluate its bioaccumulation potential and bioindication suitability. Study sites were grouped in three types: urban, agricultural and semi-natural (forests) according to land cover and anthropogenic activities in their surroundings. Concentrations of Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Ni, Pb and Zn were determined by atomic absorption spectrometry. Results highlighted higher levels of pollution (e.g. Cd, Cr, Fe, Ni and Zn concentrations in sediments) in urban and agricultural areas than in forest areas. The levels of metals in leaves were high and contents differed between sites exposed to various metal sources. The lowest concentrations of Co, Mn, Ni, Pb, Zn in plants were noted in forest areas; the highest Cd content in agricultural sites while the highest Cr, Fe, K content in urban sites. Neural networks demonstrated similarities in sediments and leaves of N . lutea in response to multi-elemental pollution. Results indicated on the possibility of using the leaves of N. lutea as an indicator of pollution in water bodies (in biomonitoring process). Eggs of Little Bitterns show high variation and their size increases with latitude.